Economic Impact of the Political Crisis in Kenya : 2008 and Beyond - World Bank (Washington, DC, 2014)
This note reviews the performance of key sectors of the Kenyan economy after the power-sharing arrangement of 2008. Declines in the agricultural, manufacturing, and services sectors considered in this note are estimates. Data collected and information interpreted provides picture of the broad orders of magnitude anticipated of the economic decline. Assuming that the power-sharing arrangement holds and the country returns to normalcy, a base case economic growth rate of about 3 percent could be expected for 2008. If a credible set of measures is steadily implemented and the fiscal constraint is managed well, these could add 1-1.5 percentage points to the base case rate of 3 percent. On the downside, continued sporadic ethnic violence, inability of coalition government to reach key decisions, and lack of donor support could result in zero or negative growth rates in 2008. The note is organized as follows. Sections I and II present the macro effects of the crisis and sectoral developments which are then used to calculate the real output expectations in 2008, as well as discuss factors that would determine the extent to which longer term prospects also are affected. Section III focuses on the poverty situation. Fiscal issues are taken up in section IV. External accounts are discussed in section V. Financial markets and issues related to investor confidence are in section VI.